The Effect of Business Capital, Financial Literacy and Social Media Usage on The Business Performance of Micro, Small and Medium Enterprises (Case Study of MSME Actors in the Culinary Sector in Jambi City) - Fadhilah, Jihan; Enggar Diah Puspa Arum; Wiralestari (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of the study is to evaluate and analyze the effect of business capital, financial literacy and social media usage on the performance of micro, small and medium enterprises culinary sector in Jambi City. Primary data collection in this quantitative research was carried out through distributing questionnaires. The sampling technique uses Stratified Random Sampling with the Proportional Stratified Sampling method. The population and sample in this study amounted to 100 respondents who were MSME actors in the culinary sector in Jambi City. The data analysis method uses PLS with the SmartPLS 3.0 software. The findings in this research are that business capital and business performance are not correlated. Meanwhile, the variables financial literacy and social media usage have a correlation with business performance